Refinement of management practices for jasmine (jasminum sambac L) in humid tropics - Smisha I S (Department of Pomology and Floriculture, College of Horticulture, 2007)
Studies were conducted at the Department of Pomology and Floriculture, College of Horticulture Vellanikkara, to find out the effect of month of pruning and fertilisers on vegetative and floral characters of J. sambac as well as post harvest trials on extending the keeping quality of flowers.